2020
DOI: 10.1007/s40121-020-00305-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-Marketing Surveillance of Adverse Events Following Vaccination with the Live-Attenuated Japanese Encephalitis Chimeric Virus Vaccine (Imojev®) in South Korea, 2015–2019

Abstract: Introduction: The live attenuated Japanese encephalitis chimeric virus vaccine (JE-CV; Imojev Ò) has been approved in South Korea for use in subjects aged C 12 months since 2015. As part of the license agreement, a post-marketing surveillance study was undertaken to actively monitor the safety profile of JE-CV in the Korean population. Methods: An observational, active safety surveillance study was conducted from 3 April 2015 through to 2 April 2019 at 12 centers in South Korea. Subjects aged C 12 months who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“… 23 , 24 When comparing Imojev and JEspect, the former presented ~30% higher odds of AEFI, though the difference was not statistically significant and unlikely to be of any clinical significance. Our study also support findings from previous JE vaccine clinical trials 15 , 16 as well as smaller post-marketing studies with passive 25 and active 26 surveillance systems that AEFIs are age-dependent and more frequent among children aged <5 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 23 , 24 When comparing Imojev and JEspect, the former presented ~30% higher odds of AEFI, though the difference was not statistically significant and unlikely to be of any clinical significance. Our study also support findings from previous JE vaccine clinical trials 15 , 16 as well as smaller post-marketing studies with passive 25 and active 26 surveillance systems that AEFIs are age-dependent and more frequent among children aged <5 years.…”
Section: Discussionsupporting
confidence: 90%
“… 27 Previous surveillance studies have found that individuals who received concomitant vaccines were more likely to report AEFIs compared to those who only received JE vaccine. 25 , 26 , 28 The evidence on AEFIs after receiving specific combinations of vaccines is sparse. Capeding et al found that infants (aged 9–10 months) who received concomitant live attenuated SA 14–14-2 JE and MMR vaccines compared to JE vaccine alone were twice as likely to develop fever, rash, diarrhea, and irritability.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Moreover, clinical studies and post-marketing surveillance all showed favorable safety profile of JE-CV (Table 1). [61][62][63][64][65][66][67][68] The most common adverse effects were injection site reaction with incidence of 6.3% to 37.8% and fever (3.6%-39.0%). Solicited adverse reactions following vaccination were most frequently reported in children younger than 24 months of age.…”
Section: Live-attenuated Chimeric Je Vaccinementioning
confidence: 99%
“…Solicited adverse reactions following vaccination were most frequently reported in children younger than 24 months of age. 63 , 68 Few serious adverse reactions had been reported, but further investigations showed unrelatedness to JE–CV vaccination.…”
Section: Safety Of Japanese Encephalitis Vaccinesmentioning
confidence: 99%